Perbedaan Jumlah Leukosit Menggunakan Hematology Analyzer Dan Modifikasi Reagen Turk Menggunakan Perasan Jeruk Nipis 2% Secara Mikroskopis - Indah Sari (jurnal kesehatan terapan sains dan teknologi, 2025)
Background : Leukocytes are white blood cells and have a cell nucleus. Leukocytes play a role in the body's defense system to resist the entry of foreign substances (antigens) that cause disease that enter the human body. Examination of the number of leukocyte cells can be done microscopically and with a hematology analyzer. The availability of Turk reagent for manual leukocyte count examination which is usually done by simple clinics or remote health center clinics is often not available, so an alternative material is needed as a substitute for Turk's solution. Lime juice(Citrus aurantifolia Swingle) is a weak acid with low acidity that can lyse erythrocytes so that it is thought to be an alternative to Turk's reagent. Objectives : to determine the difference in the number of leukocytes using Hematology analyzer and modified turk reagent using 2% lime juice microscopically. Research methods :This research was the experimental research with a research design using the Post Test Control Group Design. Sampling technique is Purposive Sampling in patients at the Sabokingking Health Center. Results : The results of the study were tested for normality and the data were normally distributed. Then data analysis was analyzed using a Paired T-Test the obtain a Sig One-Sided P of 0.386 and Two-Sided P of 0.773 means that the value of P > 0.05. Conclusion: there is a difference in the number of leukocytes using Hematology analyzer and modified turk reagent using 2% lime juice.